Alternatives to Institutionalizing the Elderly - Watson, Michael (1984)
For economic and humanitarian reasons, the present trend to institutionalize elderly people who could remain in their own homes if they were given adequate support, must be challenged. It is important that the family physician, who knows his patients' needs well, is aware of the resources available. When these are deficient, or poorly coordinated, efforts must be made to improve them. After the patient has been properly assessed, the key to proper alternate services is the availability of a coordinated continuum of care, which includes day hospitals, day therapy centres, social daycare centres and a comprehensive home care program.